2020
DOI: 10.1007/s10228-020-00744-8
|View full text |Cite
|
Sign up to set email alerts
|

‘The Bold are the Sociable’: Personality traits and laterality in an indigenous megafish, the Deccan Mahseer (Tor khudree)

Abstract: The present study explored relationships between personality traits; boldness, activity and 2 sociability, and lateralized utilization of brain hemispheres in the hatchery reared juveniles of Deccan Mahseer (Tor khudree), a game fish inhabiting the rivers of central and southern 2 India. Our results revealed a significant positive correlation between boldness and activity in 2 this species when tested in isolation. However, boldness was positively correlated with the 2 time spent near the individual conspecifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
8
1
Order By: Relevance
“…In a similar vein, shy guppies (P. reticulata) had more network connections which were stronger than those of bold fish (Croft et al, 2009), but other work with the same species found no relationship (Irving & Brown, 2013) and in male guppies, there is instead evidence of a positive correlation between sociability and boldness (Irving & Brown, 2013). Varma et al (2020) also documented a positive correlation between boldness and sociability in the fish Deccan mahseer (Tor khudree). Contrasting trends are also seen across studies that used different populations of three-spined sticklebacks (G. aculeatus), with some finding the expected negative correlation between boldness and sociability (Ward et al, 2004), but others finding no relationship (Jolles et al, 2017;Bevan et al, 2018).…”
Section: Relationship To Other Personality Traitsmentioning
confidence: 85%
See 2 more Smart Citations
“…In a similar vein, shy guppies (P. reticulata) had more network connections which were stronger than those of bold fish (Croft et al, 2009), but other work with the same species found no relationship (Irving & Brown, 2013) and in male guppies, there is instead evidence of a positive correlation between sociability and boldness (Irving & Brown, 2013). Varma et al (2020) also documented a positive correlation between boldness and sociability in the fish Deccan mahseer (Tor khudree). Contrasting trends are also seen across studies that used different populations of three-spined sticklebacks (G. aculeatus), with some finding the expected negative correlation between boldness and sociability (Ward et al, 2004), but others finding no relationship (Jolles et al, 2017;Bevan et al, 2018).…”
Section: Relationship To Other Personality Traitsmentioning
confidence: 85%
“…Ingenious experimental design may be able to estimate or manipulate motivation in a social context, and demonstrate how motivation affects the correlation of sociability with other personality traits, sociability's proximate causes, or the fitness and ecological consequences of sociability. Beyond interest from behavioural biologists, much of the research in this area uses animals as models for understanding the mechanisms behind variation in social behaviour in humans (Buffington et al ., 2016; Kondrakiewicz et al ., 2019; Brenner et al ., 2020). Additionally, many social species are important to humans for food (Ginelli et al ., 2015), as pests (Bazazi et al ., 2010; Thorlacius & Brodin, 2018) or because their populations are threatened (VanderWaal et al ., 2014; Varma et al ., 2020). Consistent variation in social tendency towards other species is also an important line of research, given the close association between our species and companion animals, particularly dogs (Jakovcevic, Mustaca & Bentosela, 2012; Kis et al ., 2014; Persson et al ., 2015, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Overall, our results only partly support and mostly contradict the behavioural syndrome concept [1,5,87] despite the high contextual and temporal overlap of the test procedures (i.e. measuring different behaviours in the same experimental compartment in sequential assays), which increases the detectability of syndromes [8,9].…”
Section: Correlations Across Different Behavioursmentioning
confidence: 74%
“…The copyright holder for this preprint this version posted June 9, 2023. ; https://doi.org/10.1101/2023.06.09.543342 doi: bioRxiv preprint correlation between sociability and boldness (Deccan mahseer, Tor khudree (21)), while others show no correlation (guppies, Poecilia reticulata (22,23)).…”
Section: Boldnessmentioning
confidence: 99%